Nongenomic roles of thyroid hormones and their derivatives in adult brain: are these compounds putative neurotransmitters? - Martin, Joseph V.; Sarkar, Pradip K. (Frontiers in Endocrinology, 2023)
We review the evidence regarding the nongenomic (or non-canonical) actions of thyroid hormones (thyronines) and their derivatives (including thyronamines and thyroacetic acids) in the adult brain. The paper seeks to evaluate these compounds for consideration as candidate neurotransmitters. Neurotransmitters are defined by their (a) presence in the neural tissue, (b) release from neural tissue or cell, (c) binding to high-affinity and saturable recognition sites, (d) triggering of a specific effector mechanism and (e) inactivation mechanism. Thyronines and thyronamines are concentrated in brain tissue and show distinctive patterns of distribution within the brain. Nerve terminals accumulate a large amount of thyroid hormones in mature brain, suggesting a synaptic function. However, surprisingly little is known about the potential release of thyroid hormones at synapses. There are specific binding sites for thyroid hormones in nerve-terminal fractions (synaptosomes). A notable cell-membrane binding site for thyroid hormones is integrin αvβ3. Furthermore, thyronines bind specifically to other defined neurotransmitter receptors, including GABAergic, catecholaminergic, glutamatergic, serotonergic and cholinergic systems. Here, the thyronines tend to bind to sites other than the primary sites and have allosteric effects. Thyronamines also bind to specific membrane receptors, including the trace amine associated receptors (TAARs), especially TAAR1. The thyronines and thyronamines activate specific effector mechanisms that are short in latency and often occur in subcellular fractions lacking nuclei, suggesting nongenomic actions. Some of the effector mechanisms for thyronines include effects on protein phosphorylation, the Na + /K + ATPase, and behavioral measures such as sleep regulation and measures of memory retention. Thyronamines promptly regulate body temperature. Lastly, there are numerous inactivation mechanisms for the hormones, including decarboxylation, deiodination, oxidative deamination, glucuronidation, sulfation and acetylation. Therefore, at the current state of the research field, thyroid hormones and their derivatives satisfy most, but not all, of the criteria for definition as neurotransmitters.